Avaliação dos efeitos citotóxicos e renais promovidos pelo veneno da serpente Bothrops alternatus - Nogueira Júnior, Francisco Assis (2017)
The snakes of the genus Bothrops sp. are responsible for the highest number of ophidian accidents in Brazil, according to the Ministry of Health. Acute kidney injury (AKI) is the severe complication most associated in these types of accidentes. The Bothrops alternatus snake is a species of medical importance responsible for ophidian accidents, predominantly in Southern Brazil. Thus, it was investigated renal changes induced by the total venom of Bothrops alternatus (Baltv) in isolated rat kidney system and kidney proximal tubule cells culture from LLC-MK2 (Monkey) and HK-2 (Human) lines. In the kidney perfusion system, Wistar rats (250 to 300 g) were used, with two experimental groups (1 μg/mL and 3 μg/mL vBalt; n = 6). There was a decrease in the perfusion pressure (PP) at the concentration of 1 μg/mL at 90 and 120 min and of 3 μg/mL at 60, 90 and 120 min. For both concentrations, renal vascular resistance (RVR) and urinary flow (UF) decreased at 90 and 120 minutes and the glomerular filtration rate (GFR) was reduced from 60 min. When the percentage of electrolyte transport was analyzed, it was observed that the tubular sodium transport (% TNa+) was reduced at 120 min in the concentration of 1 μg/mL, and at 90 and 120 min to 3 μg/ml; The tubular chloride transport (%TCl-) was also reduced at 120 min to 1μg/ml and at 60, 90 and 120 min for the concentration of 3 μg/mL; when the proximal tubular transport was analyzed, it was seen that the proximal tubular sodium transport (%TpNa+) and proximal tubular chloride transport (%TpCl-) decreased from 60 min until the end of the experiment to the concentration of 1 μg/mL, and at 60, 90 and 120 to 3 μg/mL. The histopathological analysis demonstrated the presence of significant microscopic morphological alterations, such as accumulation of proteins at the tubular and glomerular level, glomerular damage and hydropic degeneration at both concentrations studied. In the evaluation of the oxidative stress profile, it was observed that the levels of reduced glutathione (GSH) were decreased in concentrations: 1μg/mL (643.8 ± 36.31 μg/g tissue) and 3μg/mL (757.4 ± 126.7 μg/g tissue), with malondialdehyde levels (MDA) increased at concentrations of 1 μg/mL (16.42 ± 3.561 μg/g tissue) and 3 μg/mL (15.37 ± 2.237 mg /g tissue). Nitrite levels also increased in relation to the control: 1μg/mL (309.4 ± 25.29 nM /g tissue) and 3μg/mL (330.7 ± 29.19 nM/g tissue). In the culture of LLC-MK2 and HK-2 cells, the Baltv decreased cell viability at high concentrations (50, 100 and 200 μg / mL) only for LLC-MK2, on the other hand, in reduced concentrations (0,19, 0,39, 0,78, 1,56, 3,12, 6,25, 12,5, 25µg/mL), an increase in cell viability was observed, presenting an IC 50 of 221.3 μg/mL to the LLC-MK2 line. In the analysis of type of induced cell death, flow cytometry was used with Annexin V-PE and 7-AAD, and it was observed that cell death occurred predominantly due to necrosis. These results demonstrated that the venom of Bothrops alternatus altered all renal parameters and functions evaluated in the kidney perfusion model, demonstrating its direct nephrotoxic action and its cytotoxic effects in the studied cell cultures.